Boxing, jiu-jitsu, Greco-Roman wrestling and stick fencing in Barcelona. Sportsmen and social classes at the beginning of the 20th century (Revista de Artes Marciales Asiáticas, 2022)
At the beginning of the 20th century, the bourgeois class of Barcelona used sport to project the ideal of a modern, Europeanized and civilized city. In this context, physical combat activities such as boxing, Greco-Roman wrestling and jiu-jitsu appeared and were immersed in a process of sports institutionalization. This process began with the entry of these combat practices (“hand-to-hand”) in the gymnasium, a place of physical worship that was strategically institutionalized by the bourgeoisie as a device of civilization. Through primary and secondary documentary sources, this work analyzes how these combat practices were assimilated and normalized by the bourgeois class. In a critical analysis, the historical events are deconstructed and the presence of a civilizing social projection is sustained, the purpose of which was to mitigate urban violence in the streets. The use of capitalist logic projected in combat sports the commercialization of civilized violence.